Governance mechanisms, societal institutions, and State bureaucracy: concerns over societal institutions and governmental porosity - Ribeiro, José Mendes (2023)
This essay discusses participative governance mechanisms in the public  sector grounded on theories of civil  liberties, dialogical democracies, patterns of state bureaucracies, and public  governance reforms. We aimed to analyze the effects of  these issues on political agendas and public and participative governance alternatives in Brazil, emphasizing conflicts among rulers,  politicians, civil servants, interest groups,  and advocacy coalitions in dispute in  decision-making processes. The article  signals a hybrid nature of the Brazilian  democracy in which Weberian universalism  and rules of Welfare State institutions  inscribed in the 1988 constitutional matrix  operate through competition between two  other logic streams – strata inheritance of  state bureaucracy on the one hand and  initiatives in favor of horizontal and  participative governance on the other. The article  signals for a hybrid character of Brazilian  democracy where Weberian universalism  and rules of Welfare State institutions  inscribed in 1988 constitutional operates  through competition between two logics –  stratum inheritance of state bureaucracy in  one side, and initiatives in favor of  horizontal and participative governances to  the other side. Dynamic contradictions  among these for issues will define the  pattern of present competition for State  apparatus.